STRATEGI MENANGKAP PELUANG USAHA PADA PEMBUATAN SABUN CUCI PIRING DALAM RANGKA MENINGKATKAN PENDAPATAN MASYARAKAT DESA GAGAKSIPAT KECAMATAN NGEMPLAK KABUPATEN BOYOLALI - Sugiarti Sugiarti; Ariefah Yulandari; Sugiyarmasto Sugiyarmasto; Syahwa Luna Happy Nandita; Erni Febriyanti (JUPADAI : Jurnal Pengabdian Kepada Masyarakat, 2025)
Abstract Current community service activities aim to provide additional insight based on business assistance regarding strategies for obtaining opportunities in the business sector, which include: challenges and opportunities for entrepreneurship, assessing opportunities, opening a business and competitive advantages for entrepreneurs, as well as strategies for capturing business opportunities, the main causes and several shortcomings of business failure. The participant in this service activity was Mrs. PKK Gagaksipat Village, Ngemplak Boyolali. The evaluation results show that the activities‹ carried out by the Abdimas Team of lecturers and students were successful, because the participants who attended were very enthusiastic about participating in each material presentation session. By taking part in this training, mothers can not only fulfill their household needs independently with environmentally friendly dishwashing soap, but also have the potential to develop a small business from this product. It is hoped that this activity can improve skills, empower housewives, and open up additional sources of income thereby strengthening the economy of families and communities in the village.